SOFTWARE FOR ADAPTING DSPZ RECEIVERS TO THE URAN INTERFEROMETER NETWORK - Isaeva, E. A.; Lytvynenko, O. A.; Shepelev, V. A. (Одеські астрономічні публікації, 2017)
More than 10 years ago, URAN interferometer network (Megn A.V.,1997; Konovalenko A.A., 2014) had been equipped with newly designed receivers with a pass band extended up to 250 kHz and software rejection of interferences (Rashkovskii, 2012). The broadening of bandwidth of received signal increase the sensitivity of the receivers significantly and let us to investigate the angular structure about one hundred radio sources. A software package had been developed that allows: preparing a program of observations, carrying out observations automatically, making data cross-correlation, calculating visibility functions for all pairs of antennae, and fitting models of an angular structure of the sources. Data storage formats were elaborated for each stage of recording or processing. At present, new digital radio astronomy receiver DSPZ have been developed by IRA NASU (Zakharenko, 2016). The receiver allows recording an entire bandwidth of signals of a decameter range from 8 to 32 MHz. It is used at UTR-2 and URAN radio telescopes operated in a single dish mode. Application of the receivers for interferometer observation with the URAN network provides additional advantages in accuracy and sensitivity of studies. In this report we consider the data formats and synchronization methods used in URAN equipment and DSPZ receivers, and discuss algorithms of their transformation. Newly elaborated software is described, that allows selecting a set of frequency bands of signals recorded with DSPZ and converting them to the form used by the URAN software. This approach allows us to carry out the interferometer observations in an the extended frequency range provided by DSPZ and to use as much as possible the software package developed for the URAN network for data reduction.